2022
DOI: 10.51601/ijcs.v2i3.112
|View full text |Cite
|
Sign up to set email alerts
|

Socialization Of The International Certified Internship Program In Support Of The Merdeka Belajar - Kampus Merdeka Policy At The Faculty Of Teacher Training And Education, Santo Thomas Catholic University, Medan

Abstract: The internship program is an activity for students to apply knowledge, attitudes, general and specific skills in the workplace. The duration of this internship is a minimum of 6 months and can be extended according to the provisions or agreement between the original institution and the Internship Workplace. Students must be guided by internal supervisors from lecturers and external supervisors from the Internship Workplace. The purpose of this paper is to find and take an inventory of several businesses as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Research has also highlighted the importance of skills acquisition and employability among interns in various fields. Studies have shown that internships play a crucial role in preparing students for the realities of the job market, bridging the gap between academic learning and practical application (Ananda et al, 2022). By engaging in internships, students can acquire industry-specific skills, enhance their employability, and gain valuable insights into their chosen career paths.…”
Section: Opportunities Arising From Participation In International On...mentioning
confidence: 99%
“…Research has also highlighted the importance of skills acquisition and employability among interns in various fields. Studies have shown that internships play a crucial role in preparing students for the realities of the job market, bridging the gap between academic learning and practical application (Ananda et al, 2022). By engaging in internships, students can acquire industry-specific skills, enhance their employability, and gain valuable insights into their chosen career paths.…”
Section: Opportunities Arising From Participation In International On...mentioning
confidence: 99%